Genetic polymorphism of N-acetyltransferase-2, glutathione S-transferase-M1, and cytochromes P450IIE1 and P450IID6 in the susceptibility to head and neck cancer. Issue 4 (April 1998) - González, M V; Alvarez, V; Pello, M F; Menéndez, M J; Suárez, C; Coto, E
Abstract : AIMS: To analyse the allele frequencies of DNA polymorphisms at the genes for cytochromes P450IIE1 and P450IID6, N-acetyltransferase-2, and glutathione S-transferase-M1 in patients with head and neck squamous cell carcinoma, in an attempt to define genetic factors involved in the susceptibility to this cancer, which is strongly associated with tobacco consumption. METHODS: Determination of restriction fragment length polymorphism (RFLP) at cytochromes P450IIE1/P450IID6 and NAT2 genes, and the presence of homozygous deletion of the GSTM1 gene, in 200 controls and 75 head and neck cancer patients. Allelic frequencies between the two groups were compared using a chi 2 test, and odds ratio with 95% confidence intervals were calculated. RESULTS: There was no evidence of an association between alleles of CYP2D6 and CYP2E1 and head and neck cancer in our population. Similarly, frequencies of individuals lacking the GSTM1 gene did not differ between controls and patients. However, individuals with the NAT2-SA phenotype were at higher risk of developing head and neck cancer. The frequencies of the most common SA genotype (homozygous for the NAT2*5 allele) were higher in patients than in controls (27% v 15%, respectively). Slow acetylators homozygous for the NAT2*6 allele, the second most common SA allele, were also more common in patients than in controls (11% v 5%, respectively). CONCLUSIONS: Slow NAT2 activity is a risk factor possibly leading to the development of head and neck cancer in response to tobacco carcinogens.